Implementation of a basic Sonar of Echolocation for Education in Telecommunications - Criollo Sánchez, Elvis Fredy (2018)
Currently, having a sonar of echolocation in an electronic lab is complicated due to the high cost of its implementation, which is why it is proposed that the implementation of a basic sonar, using agile technologies such as the Arduino, will be used to implement this paper. Also it has a servomotor and an ultrasonic sensor, which is responsible for detecting the distance where the objects are located. The Arduino will be in charge of controlling the servomotor movements which have to be between 15 and 165 degrees. In addition, it will send the information through the serial port to a computer, in which the data will be processed and displayed using the Processing software.